Lessons on collaboration across borders. Selected problems of urban functional-areas management based on the experiences of cross-border cooperation - Szmigiel-Rawska, Katarzyna (Journal of Public Governance, 2014)
In the paper, we assume the conclusions of the analysis of cross-border cooperation apply to the design of new initiatives for cooperation and to proposals regarding urban functional areas. The analysis leads to the conclusion that external financial intervention could jeopardize existing bottom-up structures of cooperation, and that forcing the creation of new organizations can reduce the stability of existing patterns of cooperation. The author argues in favour of using strategic planning tools to stimulate voluntary cooperation in functional areas.